Kontribusi Efikasi Diri, Pengembangan Sumberdaya Guru dan Kompetensi Terhadap Kinerja Guru SMP - Lennyza Lennyza; Diko Fajri; Nuke Novariana; Elvisawati Elvisawati; Devi Yusnita; Hasrita Lubis; Nur M. Ridha Tarigan; Nilawati Nasti (TIN: Terapan Informatika Nusantara, 2023)
The aims of this study are: (1) To determine the effect of self-efficacy on teacher performance at Indra Makmu 2 Middle School, East Aceh District. (2) To determine the effect of developing teacher resources on teacher performance at SMP Negeri 2 Indra Makmu, East Aceh Regency. (3) To determine the effect of competency on teacher performance at SMP Negeri 2 Indra Makmu, East Aceh Regency. (4) To determine the effect of self-efficacy, teacher resource development, and competency on teacher performance at SMP Negeri 2 Indra Makmu, East Aceh District simultaneously. This research was carried out at SMP Negeri 2 Indra Makmu, East Aceh Regency. With a total population of 25 people. The sample in the study was determined using a total sampling technique, so the sample size was 25 people. Data collection techniques used non-test methods, with questionnaire research instruments and library studies. Data analysis using SPSS with descriptive analysis and regression analysis. The results of the study show that: (1) There is an effect of self-efficacy on teacher performance at SMP Negeri 2 Indra Makmu, East Aceh District, with a t-count > t-table, namely 2,924 > 2,059. (2) There is an effect of the development of teacher resources on teacher performance at SMP Negeri 2 Indra Makmu, East Aceh District, where the t-test > t-table ((2.222 > 2.059). (3) There is an influence of competence on teacher performance in junior high schools Negeri 2 Indra Makmu, East Aceh Regency, with t-count > t-table (2,181 > 2,059) (4) Based on the simultaneous test the independent variables have a positive and significant influence on the dependent variable, namely there is an effect of self-efficacy, resource development teachers, and competency on teacher performance at Indra Makmu Public Middle School 2, East Aceh District (5) The contribution of the independent variable to the dependent variable is 72.0%, and the rest is influenced by other variables not examined in this research